2012
DOI: 10.5483/bmbrep.2012.45.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Functional study of Villin 2 protein expressed in longissimus dorsi muscle of Korean native cattle in different growth stages

Abstract: The aim of this study was to investigate protein profiles related to the induction of adipogenesis within the bovine longissimus dorsi muscle (BLDM) by proteomic analysis. We analyzed BLDM proteins at different growth stages to clarify the physiological mechanisms of marbled muscle development in 20 head of Korean native cattle (11 month: 10 head, 17 month: 10 head). BLDM proteins were analyzed by two-dimensional electrophoresis and image analysis. Villin 2 was specifically identified by mass spectrometry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The results reveal that the cell structure may not be affected; thus, villin 2 is related with adipocyte differentiation. The result also confirmed that villin 2 is the downregulated during adipocyte differentiation (1).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…The results reveal that the cell structure may not be affected; thus, villin 2 is related with adipocyte differentiation. The result also confirmed that villin 2 is the downregulated during adipocyte differentiation (1).…”
Section: Resultssupporting
confidence: 71%
“…2F). Moreover, in Jin's study, villin 2 protein is sharply down-regulated in 3T3-L1 mouse embryonic fibroblasts after 2 days of differentiation induction (1). Therefore, 20 mM LiCl may open Wnt/β-catenin signaling after 2 days.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations